Musicians, postural quality and musculoskeletal health: A literature's review. Issue 1 (January 2017) - Blanco-Piñeiro, Patricia; Díaz-Pereira, M. Pino; Martínez, Aurora
Summary: Objective: An analysis of the salient characteristics of research papers published between 1989 and 2015 that evaluate the relationship between postural quality during musical performance and various performance quality and health factors, with emphasis on musculoskeletal health variables. Methods: Searches of Medline, Scopus and Google Scholar for papers that analysed the subject of the study objective. The following MeSH descriptors were used: posture; postural balance; muscle, skeletal; task performance and analysis; back; and spine and music. A descriptive statistical analysis of their methodology (sample types, temporal design, and postural, health and other variables analysed) and findings has been made. The inclusion criterion was that the body postural quality of the musicians during performance was included among the target study variables. Results: Forty-one relevant empirical studies were found, written in English. Comparison and analysis of their results was hampered by great disparities in measuring instruments and operationalization of variables. Conclusions: Despite the growing interest in the relationships among these variables, the empirical knowledge base still has many limitations, making rigorous comparative analysis difficult.